CHARACTERISTICS OF EARTHQUAKES IN THE SUMATRA FAULT ZONE BASED ON STRONG GROUND MOTION RECORD HISTORY - Rahmadios, Orelsha; Putra, Rusnardi Rahmat (Jurnal Applied Science in Civil Engineering, 2023)
The Sumatra Fault produces a high annual rate of earthquakes, with many large earthquakes occurring at shallow depths. The aim of this research is to understand the characteristics of earthquakes originating from the Sumatra Fault Zone based on their ground motion parameters. Ground motion earthquake recordings were obtained from accelerograph sensors in West Sumatra over the period 2008-2018. Seven earthquake accelerogram events were analyzed, consisting of EQ1 (MW 6.6), EQ2 (MW 5.4), EQ3 (MW 5.8), EQ4 (MW 5.5), EQ5 (MW 5.5), EQ6 (MW 5.7), and EQ7 (MW 5.2). The research results indicate that PGA values range between 2-36 Gal for the horizontal component and 1.5-10 Gal for the vertical component. The average frequency content of the earthquakes ranges from 0.3-10 Hz. The PSA values for EQ1, EQ2, EQ3, EQ4, EQ5, EQ6, and EQ7 are 0.009 g, 0.177 g, 0.016 g, 0.054 g, 0.057 g, 0.027 g, and 0.033 g, respectively, which are still far below the EDRS SNI 1726 2019. The response spectra of EQ2, EQ4, EQ5, and EQ7 recorded in the city of Padang have high amplitudes in the period range of 0.06-0.2 seconds. Meanwhile, EQ1, EQ3, and EQ6 recorded in the city of Bukittinggi have high amplitudes in the period range of 0.5-1.2 seconds. The Arias intensity parameters range from 0.03-0.61 cm/s for the horizontal component and 0.02-0.09 cm/s for the vertical component.